SINTESIS DAN KARAKTERISASI NANOKOMPOSIT TIO2-SELULOSA DARI LIMBAH AMPAS TEBU - Cindhy Novita Sari; Dina Kartika Maharani (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
Sugarcane bagasse is an abundant agricultural waste in Indonesia, reaching more than 750,000 tons annually, yet it remains underutilized. It contains a high cellulose content of up to 52.7%, one of the highest among agricultural residues. Considering its high fiber content and wide availability, sugarcane bagasse has significant potential to be recycled into high-value materials, including nanocellulose, a nanoscale biopolymer with high surface area, mechanical strength, and crystallinity. This study explores the utilization of cellulose derived from sugarcane bagasse, which was subsequently composited with titanium dioxide (TiO₂) nanoparticles to form nanocomposites. Cellulose isolation was carried out using a combined chemical and mechanical method involving alkali treatment, bleaching, and acid hydrolysis, followed by ultrasonication. The nanocomposite synthesis was performed through a wet dispersion method using a water–ethanol mixture. XRD analysis confirmed the successful isolation of nanocellulose, as indicated by an increase in crystallinity index from 51.37% to 70.55% after isolation, with crystal sizes in the nanometer range, that is 4.31 nm for nanocellulose and 35.41 nm for the nanocomposite. FTIR characterization corroborates the success of isolation, showing a decrease in the intensity of functional groups associated with amorphous components such as C=O and aromatic C=C, from 0.0181 to 0.0131 and from 0.0314 to 0.0140, respectively.